2011
DOI: 10.1029/2010gl046474
|View full text |Cite
|
Sign up to set email alerts
|

Rapid poleward range expansion of tropical reef corals in response to rising sea surface temperatures

Abstract: [1] Rising temperatures caused by climatic warming may cause poleward range shifts and/or expansions in species distribution. Tropical reef corals (hereafter corals) are some of the world's most important species, being not only primary producers, but also habitat-forming species, and thus fundamental ecosystem modification is expected according to changes in their distribution. Although most studies of climate change effects on corals have focused on temperatureinduced coral bleaching in tropical areas, polew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
325
5
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 393 publications
(355 citation statements)
references
References 25 publications
24
325
5
1
Order By: Relevance
“…As predicted, corals have already extended their latitudinal range pole-wards in several locations such as Japan and eastern Australia (Booth et al, 2007;Yamano et al, 2011;Baird et al, 2012), although range expansion can be accompanied by reduced symbiont diversity (Grupstra et al, 2017). The ability and rate of this range expansion will be key in determining the ability of high-latitude locations to act as refugia.…”
Section: High-latitude Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…As predicted, corals have already extended their latitudinal range pole-wards in several locations such as Japan and eastern Australia (Booth et al, 2007;Yamano et al, 2011;Baird et al, 2012), although range expansion can be accompanied by reduced symbiont diversity (Grupstra et al, 2017). The ability and rate of this range expansion will be key in determining the ability of high-latitude locations to act as refugia.…”
Section: High-latitude Environmentsmentioning
confidence: 99%
“…Although poleward range expansion of tropical coral has been documented in several geographically different locations (e.g., Yamano et al, 2011;Baird et al, 2012), such information for other potential refuge environments is currently lacking. Thus, we do not know if all corals could utilize potential refuge services as they may lack the traits needed to survive.…”
Section: The Potential Of Refuge Environmentsmentioning
confidence: 99%
“…Its massive bloom sometimes develops extensively in late spring [e.g., Kai et al, 1999]. The south coast of Honshu is also the northern limit of tropical reef corals' habitat in the North Pacific [Yamano et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…Combining the uncertainties from differences in the warming trends and in the decadal variability among the models, we predicted the timing of temperate coral Both uncertainties in the predictions and the dynamics of corals require long-term monitoring to reveal the dynamics from new recruitment of colonies and establishment of communities in response to SST warming, especially for specifi c indicator species such as Acropora hyacinthus, Acropora muricata, Acropora solitaryensis, and Pavona decussata defi ned by Yamano et al (2011).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of 80 years of national records for temperate areas in Japan, as well as the studies above, Yamano et al (2011) showed the fi rst large-scale evidence of the poleward range expansion of modern corals in response to SST warming. They found that the speed of these expansions reached up to 14 km/year, far greater than that for other biological species.…”
Section: Introductionmentioning
confidence: 99%